Optimising circuit design for gravity gold recovery - Staunton, William; Bax, A. (The Canadian of Mining, Metallurgy and Petroleum, 2012)
To determine the optimal circuit configuration for gravity gold recovery consideration should be given to a range of factors in addition to the efficiency of the gravity circuit, including capital costs, ease of operation and impact on comminution. The most common gravity gold circuits utilise a centrifugal concentrator treating a portion of the hydrocyclone underflow. This paper will examine this option and alternative circuit configurations to illustrate the effect of various gravity circuit feed and tailings configurations on the equipment sizing, capital costs, operating costs, water balance, comminution efficiency and gravity gold recovery. The optimum circuit configuration can provide reduced capital and operating costs, maximise gravity gold recovery and improve comminution efficiency.